Association Between Components of Cognitive Reserve and Serum BDNF in Healthy Older Adults - Collins, Jessica M.; Hill, Edward; Bindoff, Aidan; King, Anna E.; Alty, Jane; Summers, Mathew J.; Vickers, James C. (Frontiers in Aging Neuroscience, 2021)
Background: The brain derived neurotrophic factor (BDNF) protein has been shown to have a prominent role in neuron survival, growth and function in experimental models, and the BDNF Val66Met polymorphism which regulates its expression has been linked to resilience toward the effects of aging on cognition. Cognitively stimulating activity is linked to both increased levels of BDNF in the brain, and protection against age-related cognitive decline. The aim of this study was to investigate the associations between serum BDNF levels, the BDNF Val66Met genotype and cognitively stimulating activities in early and mid-life, measured with the Lifetime of Experiences Questionnaire (LEQ). Methods: Serum BDNF levels were measured cross-sectionally in 156 participants from the Tasmanian Healthy Brain Project cohort, a study examining the potential benefits of older adults engaging in a university-level education intervention. Multiple linear regression was used to estimate serum BDNF’s association with age, education, gender, BDNF Val66Met genotype, later-life university-level study and cognitively stimulating activities measured by the LEQ. Results: Serum BDNF in older adults was associated with early life education and training, increasing .007 log(pg/ml) [95%CI .001, .012] per unit on the LEQ subscale. Conversely education and training in mid-life was associated with a -.007 log(pg/ml) [-.012, -.001] decrease per unit on the LEQ subscale. Serum BDNF decreased with age (-.008 log(pg/ml) [-.015, -.001] per year), and male gender (-.109 log(pg/ml) [-.203, -.015]), but mean differences between the BDNF Val66Met polymorphisms were not significant (p = .066). All effect sizes were small, with mid-life education and training having the largest effect size (ηp2 = .044). Conclusion: Education in both early and mid-life explained small but significant amounts of variance in serum BDNF levels, and more than age or gender. These effects were opposed and independent, suggesting that education at different stages of life may be associated with different cognitive and neural demands. Education at different stages of life may be important covariates when estimating associations between other exposures and serum BDNF.